Comment on: Electoral contests, incumbency advantages, and campaign finance - Ivan Pastine; Tuvana Pastine (University College Dublin, UCD School of Economics, 2009)
This paper completes Meirowitz (2008) by analyzing the effect of a cap on political campaign spending in an environment where voters have initial preferences over political candidates. The policy implications are starkly different from the previously analyzed case where voters are indifferent between candidates in the absence of campaign spending. We find that a spending cap always favors the a priori popular candidate. This result holds irrespective of whether it is the incumbent or the challenger who is able to more effectively generate and spend contributions.
hdl:10197/2611
Keywords: 330; Campaign finance reform; Spending limit; Expenditure limit; Incumbency advantage; Clean elections